PENGEMBANGAN MODUL AJAR MATERI CROSS PRODUCT BERBASIS PROBLEM BASED LEARNING TERKAIT KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Iklimah Nur Azizah; Yayu Laila Sulastri; Deti Ahmatika (UJMES (Uninus Journal of Mathematics Education and Science), 2022)
This research is motivated by the existence of a driving school program, the lack of teaching materials used in schools, and the difficulties of students in solving cross product problems, as well as learning that is only centered on educators. So it is necessary to develop cross product teaching materials whose learning is centered on students. The teaching material developed in this research is a cross product teaching module based on problem based learning related to mathematical problem solving abilities. This study aims to determine the level of validity, effectiveness, and practicality of teaching modules. The research method used is Design-based-Research (DbR) with the plomp model. Sources of data in this study are validators of media experts, material experts, students, respondents of mathematics teachers. Based on the results of the analysis carried out, it can be concluded that the teaching module developed is valid, small group trials are effective and the response from educators is very practical. It is recommended that further research be carried out on a large scale, using different mathematical abilities and learning models.